Development of biosensor for the early detection of tuberculous meningitis in infants - Kim, Dabin (Stellenbosch : Stellenbosch University, 2025)
Kim, D. 2025. Development of biosensor for the early detection of tuberculous meningitis in infants. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/1a4ddd6e-330f-49c3-8f53-8d8591e4ee09